Executive Compensation in Controversial Industries: A Qualitative Study of Pay-for-Performance Sensitivity in Sin Companies - Grace Yulianti; Dadang Irawan; Tanti Sugiharti (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review examines the pay-for-performance sensitivity in managerial compensation within controversial industries, often referred to as